Correction of the aortic arch hypoplasia in newborn babies, suffering complete form of atrio-ventricular septal defect - Ya. P. Тruba; А. А. Dovhaliuk; І. V. Dzyurii; P. А. Danchenko; О. S. Golovenko; V. V. Lazoryshynets (Клінічна хірургія, 2020)
Objective. Tactics of treatment and results of the hypoplasia of the aortic arch correction in newborn babies with complete form of atrio-ventricular septal defect were studied.